ECONOMIC THEORY: CRITICAL NOTES AND ADDITIONS TO SOME CATEGORIES - A. Urunov (Publishing House of the State University of Management, 2017)
In article it is proved and specified fundamental categories of the economic theory such as «economy», «market» and «the pricing mechanism» a misinterpretation of which conducts to the reader's delusion. The main arguments and the author's arguments in contents of these terms taking into account new realities in market economy are adduced.